(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Entrepreneurship is a skill for discovering innovative opportunities, taking risks and managing the business. The Nation could have all the critical resources like land, labor, capital, technology, investor friendly environment, government policies, procedures and other inputs but the development and dynamism for growth and sustained continuous economic progress can be provided primarily by entrepreneurs.